Drawing for graphic design : understanding conceptual principles and practical techniques to create unique, effective design solutions - Samara, Timothy (Rockport Publishers, 2012)
"Here is a complete, comprehensive drawing reference for design students and professionals alike who want to implement drawing as a professional tool. In Drawing for Graphic Design, Timothy Samara empowers readers to add drawing to their design vocabulary, featuring case studies of commercial projects from start to finish along with a showcase of real-world projects that integrate drawing as an intrinsic part of their visual communication. Filled with original author drawings and sketches, it's a must-have reference that will benefit designers of all levels"